NILAI-NILAI BUDAYA JAWA SEBAGAI MEDIA PROMOSI PARIWISATA DI DAERAH ISTIMEWA YOGYAKARTA - Akhir Lusono (Jurnal Pendidikan Seni dan Industri Kreatif, 2020)
The cultural tourism sector has a very important role in the income of a country and for areas that have tourism potential. Tourism is also earmarked for job creation for local communities. However, during the Covid-19 pandemic, tourists visiting places of attractions in Yogyakarta show a drastic decline in numbers. The purpose of this study is to describe the values of Javanese culture to promote tourism and to determine a tourism marketing strategy model that may present the excellence and uniqueness of Javanese culture in Yogyakarta. The collection of data and information was carried out by distributing questionnaires to 480 tourists who came to Yogyakarta. Descriptive analysis was done using SPSS 22.0 and SWOT analysis. The results of the sudy demonstrate that Javanese culture values can be used as a medium for promoting tourism in Yogyakarta. However, some improvements or strategies are still needed to increase tourist attractiveness. It is expected that the results of the study may assist the Yogyakarta government and tourism business stakeholders to increase the tourism potential of Javanese culture values and establishing strategies in developing tourism potential to attract tourists visiting Yogyakarta as well